KUALITAS PELAYANAN PUBLIK OLEH DESA KUAPAN KECAMATAN TAMBANG TAHUN 2024 - Maharani, Syahdia; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Public service is a crucial indicator for achieving effective, efficient, and accountable village governance. However, public service practices at the village level still face various challenges, including limited infrastructure, low information transparency, and public complaints regarding the speed and accuracy of administrative services. This study aims to analyze the quality of public services provided by the Kuapan Village government, Tambang District, Kampar Regency, in 2024. The study employed a quantitative approach with descriptive methods. Primary data were obtained through a Likert-scale questionnaire distributed to 60 community respondents who had received services at the Kuapan Village Office, supported by observation and documentation. Data were analyzed using descriptive statistics using SPSS software to obtain an overview of the frequency distribution and percentage of respondents' responses. The results indicate that the quality of public services in Kuapan Village is categorized as quite good based on five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Of the five dimensions of public service quality, the dimensions that most satisfied the Kuapan Village community were responsiveness, assurance, and empathy. However, weaknesses remain in information transparency, limited waiting rooms, and suboptimal utilization of infrastructure. In conclusion, public services in Kuapan Village have met most service quality indicators, but improvements are needed in terms of staff professionalism, facility provision, and service transparency to achieve higher quality public services. .Keywords: Public Services, Village, Quality